2013
DOI: 10.1002/eji.201242842
|View full text |Cite
|
Sign up to set email alerts
|

4–1BB signal stimulates the activation, expansion, and effector functions of γδ T cells in mice and humans

Abstract: We show here that the expression of 4-1BB is rapidly induced in γδ T cells following antigenic stimulation in both mice and humans, and ligation of the newly acquired 4-1BB with an agonistic anti-4-1BB augments cell division and cytokine production. We further demonstrate that γδ rather than αβ T cells protect mice from Listeria monocytogenes (LM) infection and 4-1BB stimulation enhances the γδ T-cell activities in the acute phase of LM infection. IFN-γ produced from γδ T cells was the major soluble factor reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Only cultures that grew in at least one of the two conditions are represented in Figure 3B. Since NK cells and γδ TCR + T cells can also express 4-1BB, we stained for their presence in primary cultures to determine if the a4-1BB antibody being used was stimulating their growth (33,34). Indeed we found that three cultures with a4-1BB were enriched with a CD3 − CD56 + population that was a greater proportion of the culture than CD3 + TIL (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only cultures that grew in at least one of the two conditions are represented in Figure 3B. Since NK cells and γδ TCR + T cells can also express 4-1BB, we stained for their presence in primary cultures to determine if the a4-1BB antibody being used was stimulating their growth (33,34). Indeed we found that three cultures with a4-1BB were enriched with a CD3 − CD56 + population that was a greater proportion of the culture than CD3 + TIL (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Correia and colleagues [17] reported that phosphoantigens alone were not able to activate gd T cells and that the addition of a high dose of IL-2 was crucial for complete gd T cell activation. Recent studies demonstrated that engagement of a variety of costimulatory molecules, including CD80 and 4-1BBL, also known as CD137L, promotes the proliferation and survival of peripheral Vg9Vd2 T cells [18][19][20]. Moreover, mature DCs, pretreated with aminobisphosphonate, were able to induce the amplification of pure gd T cells that fail to activate in cancer patients [21], suggesting that stimulatory signaling through multiple costimulatory receptors can activate and expand the gd T cells.…”
Section: Introductionmentioning
confidence: 99%
“…IL-17A-and IFN-g-producing cells have a protective role in the bacterial infection, in which IL-17 helps in the recruitment of neutrophils, whereas IFN-g helps in the early innate response [58,73]. 4-1BB is another TNFR superfamily molecule expressed on activated gd T cells and stimulates the activation, expansion, and effector function of gd T cells [74]. These studies suggest that TNF superfamily members play an important role in the development and function of gd T cells.…”
Section: Mechanism Of Gd T Cell Functionmentioning
confidence: 99%